MENINGKATKAN KETERAMPILAN KERJASAMA MENGGUNAKAN MODEL SPIRIT DAN MEDIA TTS DI SDN 3 PALAM BANJARBARU - Elprida Sitompul; Diani Ayu Pratiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Students' failure to cooperate is a problem in this research. This is caused by students who cannot solve problems and the lack of diverse learning models and media. To overcome this problem, the SPIRIT model and TTS media are used. The aim of this research is to improve students' ability to work together. Class III students at SDN 3 PALAM Banjarbaru, totaling 12 people, were the research subjects. Qualitative data from student collaboration skills observation sheets were analyzed for this research, using descriptive techniques, tables and percentage interpretation. The results studied showed an increase from 42% to 92% from meeting 1 to 4, so that the SPIRIT model and TTS media could improve students' collaboration skills from meeting 1 to meeting 4 with the criteria of "very skilled". The results also show that the SPIRIT model and TTS media can be used as a reference for learning models.